The Right to Healthcare under European Law (Diametros, 2017)
Too often, the right to healthcare has been considered an illusory right that is not even a legal right, but merely an aspirational norm that cannot be adjudicated before the court. In modern human rights law, considering individual and social rights as interdependent and indivisible, such an approach is untenable. Both legal doctrine and recent case law from domestic and international courts have elaborated and confirmed the specific obligations under the right to healthcare, countering the general complaint of “shrouded vagueness”. Landmark cases have even provided a functional remedy to enforce individual healthcare claims successfully. This paper will examine the revised legal status and content of such a right to healthcare from a European perspective.